Long-term exposure to fine particulate matter and incident asthma among elderly adults - Lee, Dong Wook; Han, Chang woo; Hong, Yun Chul; Oh, Jong Min; Bae, Hyun Joo; Kim, Soontae; Lim, Youn Hee (Chemosphere, 2021)
Rationale: Although an association of fine particulate matter (PM2.5) with asthma incidence has been assumed, there is insufficient evidence regarding the effect of long-term exposure to PM2.5 on incident asthma among elderly adults. Objectives: This study aimed to investigate an association between long-term exposure to PM2.5 and incident asthma among elderly adults in South Korea. Methods: Adults ≥65 years of age (n = 1,220,645) who did not visit hospitals for asthma during a washout period (between 2008 and 2010) were followed up until 2016 using data from the National Health Insurance System in South Korea. Incident asthma was defined as the number of patients with a primary diagnostic code of asthma who visited hospitals more than twice. We linked the health data with district-level PM2.5 concentrations and estimated hazard ratios (HRs) and 95% confidence intervals (CIs) for incident asthma after adjusting for potential confounders in time-varying Cox proportional hazard models. Measurements and main results: Over 5,942,256 person-years, 54,522 patients developed asthma, with an incidence of 9.2 cases/1000 person-years. A 10 μg/m3 increase in the 36-month mean PM2.5 concentration was significantly associated with a 9% increase in incident asthma (HR = 1.09, 95% CI: 1.04–1.14). This association was found to be robust for different definitions of incident asthma and washout periods. Conclusion: Long-term exposure to PM2.5 was associated with the incidence of asthma in elderly adults. This finding provides evidence of an association between PM2.5 and adult-onset asthma.
Keywords: Confidence interval; Cox proportional hazard model; Elderly adults; Fine particulate matter; Fine particulate matter (PM2.5); Long term exposure; PM2.5 concentration; Time varying; Adult; Aged; Air Pollutants; Air Pollution; Asthma; Environmental Exposure; Humans; Incidence; Particulate Matter; Republic of Korea; Asthma; Cohort studies; Elderly adults; Incidence; Particulate matter